Weed Diversity in Irrigated Rice Field in Mulyorejo Village, Malang City, Indonesia: Keanekaragaman Gulma di Areal Pertanaman Padi Sawah Beririgasi di Kelurahan Mulyorejo, Kota Malang, Indonesia - Az-Zahro, Aisyah; Maulidia, Eva; Refia, Farah Audifa; Rahayu, Jihan Chandra Hesti; Sokawati, Nowita Ayu; Anggraini, Putri; Ardhiyanti, Virdiana Intan; Fardhani, Indra (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2022)
Weeds that grow around irrigated rice fields can affect the growth of rice plants. This study aims to determine the diversity of weeds in the rice fields of Mulyorejo Village, Malang City, Indonesia. The research was conducted from October - November 2022. The research used a survey with direct descriptive and exploratory methods. The study used a survey method with descriptive and direct exploration methods on an area of 677 m2 at an altitude of 478 m above sea level. Observations were made on weed species, dominance, and diversity index. The results showed that 13 species of weeds were found in the irrigated rice fields of Mulyorejo Village, Malang City, which was dominated by water clover (Marsilea crenata) (20.42%), which is classified as a broadleaf weed. The dominant weed was taro (Alocasia macrorrhizos) (SDR = 5.33). The minor weed is water lactic (Ludwigia decurrens). The rice field weed diversity index is 1.989, classified as moderate. Knowing the types of weed diversity in rice fields in Mulyorejo, it is hoped that it can facilitate the optimal handling process.